Cyclic RGD peptide-modified liposomal drug delivery system: enhanced cellular uptake in vitro and improved pharmacokinetics in rats - Chen Z (Dove Medical Press, 2012)
Zhongya Chen,1,2 Jiaxin Deng,1,2 Yan Zhao,1,2 Tao Tao1,21National Pharmaceutical Engineering Research Center, 2Shanghai Institute of Pharmaceutical Industry, China State Institute of Pharmaceutical Industry, Shanghai, People's Republic of ChinaBackground: Integrins αvβ3 and αvβ5, both of which specifically recognize the Arg-Gly-Asp (RGD) motif, are overexpressed on many solid tumors and in tumor neovasculature. Thus, coupling the RGD motif to the liposomal surface for achieving active targeting can be a promising strategy for the treatment of tumors.Methods: Cyclo(Arg-Gly-Asp-D-Phe-Cys) (cRGD) was covalently coupled with the liposomal membrane surface, followed by coating with poly(ethylene glycol) (PEG) using the post-insertion technique. The coupling efficiency of cRGD was determined. Doxorubicin as a model anticancer drug was loaded into liposomes using an ammonium sulfate gradient method to investigate the encapsulation efficiency, cellular uptake by the integrin-overexpressing human glioma cell line U87MG in vitro, and pharmacokinetic properties in Sprague-Dawley rats.Results: cRGD was conjugated to the liposomal surface by a thiol-maleimide coupling reaction. The coupling efficiency reached 98%. The encapsulation efficiency of doxorubicin in liposomes was more than 98%. The flow cytometry test result showed that cRGD-modified liposomes (RGD-DXRL-PEG) had higher cell uptake by U87MG cells, compared with nontargeted liposomes (DXRL-PEG). The cellular uptake was significantly inhibited in the presence of excess free cRGD. Both the targeted (t1/2 = 24.10 hours) and non-targeted (t1/2 = 25.32 hours) liposomes showed long circulating properties in rat plasma. The area under the curve of the targeted and nontargeted liposomes was 6.4-fold and 8.3-fold higher than that of doxorubicin solution, respectively.Conclusion: This study indicates preferential targeting and long circulating properties for cRGD-modified liposomes in vivo, which could be used as a potential targeted liposomal drug delivery system to treat human glioma.Keywords: drug targeting, doxorubicin, covalent coupling, sterically stabilized liposomes, human glioma, post-insertion